Concomitant Renal Cell Carcinoma and Hematologic Malignancy in Immunosuppressed Patients. (May 2016) - Johnson, Lewis; Bylund, Jason; Strup, Stephen; Howard, Dianne; Gul, Zartash; Khan, Muhammad Waqas; Venkatesh, Ramakrishna
ABSTRACT : Objectives: : Treatment of a renal mass in patients with hematologic malignancy or on immunosuppression can be complex and is not well defined. Surgical excision or thermal ablation of renal mass is generally recommended in view of concern for tumor progression in immunosuppressed patients. We report our management decision experience in patients and literature review on concomitant renal and hematologic malignancy. Materials and Methods: : A retrospective medical record review of patients with renal cell carcinoma (RCC) and a hematologic malignancy over 3 years at our University Hospital was performed. Data were collected including patient's demographics, renal tumor and hematologic malignancy characteristics (stage, pathologic subtype, time of diagnosis, treatment type and prognosis). Surgical and medical management of each malignancy was reviewed and perioperative and overall outcomes are reported. Results: : In total, 6 patients were identified with RCC and a hematologic malignancy of which 4 were on immunosuppressive therapy. A total of 5 patients had leukemia and 1 patient had multiple myeloma. Most kidney tumors were stage I, 83%; and 80% were Fuhrman grade II. There was equal distribution of clear cell and papillary‐type RCC. All but 1 patient had undergone nephron‐sparing surgery. Overall, 50% of our patients died within 1 year after renal surgery for pT1 a tumors from causes that are unrelated to renal cancer. Conclusions: : Our small cohort showed significant mortality in patients with hematologic malignancy on immunosuppression, who had their renal mass treated with surgical excision or thermal ablation. However, this mortality was not secondary to surgical procedure itself. The prognosis of the hematologic malignancy might dictate the management of RCC.